Pengaruh Naungan dan Zat Pengatur Tumbuh terhadap Pertumbuhan dan Hasil Tanaman Kentang Kultivar Atlantik di Dataran Medium - Hamdani, Jajang Sauman; ,, Sumadi; Suriadinata, Yayat Rochayat; Martins, Lourenco (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2016)
ABSTRACTUse of shade on the cultivation of potato in medium altitude is expected to reduce both light intensity and temperature, and therefore is more suitable for potatoes to grow in medium altitude. While the use of growth regulators subtances improving the process of assimilate distribution from the leaves to the tuber. Therefore use of shade followed by plant growth regulators applications are expected to increase of growth and yield. The objectives of the experiment were to determine growth and yield of potato cultivar Atlantik grown at medium altitude with different types of shading and plant growth regulators. The experiment was conducted at an experimental station of the Faculty of Agriculture, Padjadjaran University, Jatinangor, Sumedang, at an altitude 685 m asl. The experiment was arranged in a split plot design consisting of two factors and three replications. The main plots were types of shading (without shading, paranet 45%, UV polyethylene, and corn plant) and the sub plots were combination of plant growth regulators (benzylaminopurine + paclobutrazol), (benzylaminopurine +chloro choline chloride), benzylaminopurine, paclobutrazol, chloro choline chloride). The results showed that the effect of interaction between shading and plant growth regulator on growth and yield of the potato were not significant. Paranet shade and corn plant shade increased plant height, leaf area index, tuber weight per plant, yield per hectar and tuber grade A of potato cultivar Atlantik. Corn plant shading gave potato yield 21.6 ton ha-1 with 64% grade A tuber. Paclobutrazol decreased potato plant height, but increased number of tuber per plant and yielded highest tuber weight of 702.1 per plant (23.3 ton ha-1 ), with 70.9% grade A tuber. Keywords: Benzylaminopurine, microclimate, paclobutrazol, temperature